2019
DOI: 10.1002/mma.5665
|View full text |Cite
|
Sign up to set email alerts
|

Modelling and analyzing the epidemic of human infections with the avian influenza A(H7N9) virus in 2017 in China

Abstract: in mainland China, a novel avian influenza A(H7N9) virus began to infect humans, followed by the annual outbreaks, and had aroused severe fatality in the infected humans. After introducing the statistical characteristics including the geographical distributions of the outbreaks, a SEV-SIRS eco-epidemiological model is established and analyzed. In this model, the factor of virus in environment is incorporated into the model as a class; the vaccine measure in poultry is taken into account in purpose of assessing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…In [27] , They analyzed the global dynamics of the SIRS model with (1.2) as well as demonstrated that as time progresses, numbers of infected persons converge toward zero or the disease is persistent. Chen and Wen [28] used (1.2) to characterize the transmission between human and poultry, which conform the effect of human intervention.
Fig.
…”
Section: Introductionmentioning
confidence: 99%
“…In [27] , They analyzed the global dynamics of the SIRS model with (1.2) as well as demonstrated that as time progresses, numbers of infected persons converge toward zero or the disease is persistent. Chen and Wen [28] used (1.2) to characterize the transmission between human and poultry, which conform the effect of human intervention.
Fig.
…”
Section: Introductionmentioning
confidence: 99%